Thriving! a manual for students in the helping professions - Echterling, Lennis G. 1948-; Presbury, Jack H.; Cowan, Eric W.; Staton, A. Renee; Sturm, Debbie C.; Kielty, Michele; McKee, J. Edson; Stewart, Anne L. 1951 November 25-; Evans, William F. (SAGE Publications, Inc., 2016)
Written in a conversational and engaging style, this updated and expanded Third Edition of Thriving! helps future counselors and therapists to succeed in their training and professional development throughout their graduate careers. This informative and inspirational book includes an overview of the literature, personal accounts from students, practical tips/activities, and the latest coverage of such topics as advances in neuroscience research, crisis intervention, and more!